Proceedings of the 2015 AASOG Conference: Reducing Disparities in Sarcoidosis through Personalized Care and Increased Detection - Hamzeh, Nabeel; Judson, Marc A; Maier, Lisa A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
The 2015 annual meeting of the Americas Association of Sarcoidosis and Other Granulomatous Disorders (AASOG) was held on September 25th and 26th at the University of Colorado Anschutz Medical Campus in Aurora, CO, U.S.A.  The meeting was hosted by National Jewish Health and the theme of the meeting was “Reducing Disparities in Sarcoidosis through Personalized Care and Increased Detection”. The meeting was endorsed by the American Thoracic Society (ATS) and the Foundation for Sarcoidosis Research (FSR), and was conducted through support provided by the National Institutes of Health (NIH), particularly the National Heart Lung and Blood Institute (NHLBI), and an unrestricted educational grant from Mallinckrodt, Inc. The meeting participants were predominantly from North America, and included preeminent experts and emerging clinical scientists engaged in sarcoidosis research. The AASOG meeting was held in parallel with a sarcoidosis patient conference that was organized and funded by the Foundation of Sarcoidosis Research (FSR). The AASOG talks covered various state-of-the-arts topics related to sarcoidosis research and care;  most notable were talks focusing on preliminary and emerging data from the Genomic Research in Alpha-1 antitrypsin Deficiency and Sarcoidosis (GRADS) study, recent novel immunological and genomic discoveries that further our understanding of sarcoidosis disease pathogenesis, results from clinical trials in sarcoidosis and proposals of novel therapeutic targets for the treatment of sarcoidosis, the introduction of the FSR sponsored clinical studies network, insights from other granulomatous diseases, and a focus on extra-pulmonary sarcoidosis, particularly cardiac disease, small fiber neuropathy, and fatigue. A session dedicated to scientific abstracts from predominantly junior investigators and five oral abstract presentations brought the conference to a conclusion. A brief overview and selected excerpts of the 2015 AASOG meeting proceedings are provided herein.